Pengembangan E-Modul Berbasis Warisan Budaya Tak Benda (WBTB) Lamongan pada Tema 3 Subtema 1 Kelas V Sekolah Dasar - Lola Viska Ardani; Priyono Tri Febrianto (Yayasan Arrahman Nahdlatul Wathan, 2024)
The purpose of this study was to develop a valid, practical, and effective Lamongan-based Intangible Cultural Heritage (WBTB) based e-module on theme 3, sub-theme 1 of grade V elementary school. This study uses a 4D development model with 4 stages, namely (1) define (definition), (2) design (planning), (3) develop (development), and (4) disseminate (dissemination). The subjects of this study were fifth grade students at SDN I Tambakrigadung. Based on the validation results of linguists, material experts, teaching material design experts, and learning design experts, the average result is 88.4% with very valid criteria. Practical results were obtained from the implementation of learning through teacher activity observation sheets and student activity observation sheets of 97.3% with very practical criteria. Effectiveness results obtained from student learning outcomes. Student completeness shows a percentage of 100% with classical completeness criteria ≥ 85% fulfilling the KKM. It can be concluded that the development of an e-module based on the Lamongan Intangible Cultural Heritage (WBTB) theme 3 sub-theme 1 is appropriate for use in learning.